China’s Publishing Industry in the Era of Big Data - Zhang, Li. author. aut Link
X, 206 p. 123 illus.
Keywords: This book introduces China’s current publishing industry in the new era, especially when facing the big challenge from social media and technology transformation. Based on the calculation for the first time, the book and overall size of the content data of publications in China, the book presents 15 cases of Chinese publishers looking for opportunities to develop business, using the technology of big data and Internet. For global readers, it may help to build an overview on China's publishing industry and business innovation cases of media companies. .